Friction - Brown, Sandra 1948- (New York Grand Central Publishing, 2015)
Crawford Hunt wants his daughter back. Following the death of his wife four years ago, Crawford, a Texas Ranger, fell into a downward spiral that left him relegated to deskwork and with his five-year-old daughter Georgia in the custody of her grandparents. But Crawford has cleaned up his act, met all the court imposed requirements, and now the fate of his family lies with Judge Holly Spencer. Holly, ambitious and confident, temporarily occupies the bench of her recently deceased mentor. With an election upcoming, she must prove herself worthy of making her judgeship permanent. When a masked gunman barges in during the custody hearing with his sights on the judge, Crawford reacts instinctually and goes after him. But authorities apprehend the wrong man, and the real gunman remains unknown, at large, and a threat. Will this take-charge lawman jeopardize his chances of custody by going after the would-be assassin? And will this unlikely pair be able to deny the forbidden attraction building between them?
Keywords: Single fathers -- Fiction; Women judges -- Fiction; Man-woman relationships -- Fiction; Choice -- Fiction; Courage -- Fiction; Secrets -- Fiction; Custody of children -- Fiction; Romantic suspense fiction; Fiction